Musical Instruments of the Turkic Peoples of the Volga Region and Urals - Khayrullina, Gulnara (Lietuvos istorijos studijos, 2023)
National musical instruments are part of the culture and history of the people. They reflect the characteristics, temperament and mentality of the people, the conditions for their formation as an ethnos. Variety, rich sound, unusual melody pattern – national musical instruments create all this. Every ancient musical culture has its origins in ancient rites. Folk music of the Turkic peoples of the Volga region and the Urals was no exception. Singing was accompanied by pagan and mystical sacraments, holidays, household and daily rituals such as hunting, harvesting and much more, including military campaigns.The sound of folk instruments has a specific musical pattern and voice that distinguishes the musical instruments of the Turkic peoples from other ethnic groups that have settled since ancient times in the Urals and the Volga region. This is due to the fact that the Tatars and Bashkirs have always preferred melodic musical instruments that allow performing a branched, rich melody in a wide range. Although the list of musical instruments has about fifty varieties, this article analyses the most characteristic and ancient ones.
Keywords: the Turkic peoples of the Volga region; Musical instruments; music culture; ethnic group; kurai; Psaltery; kubyz; Dumbra; Zurna; Saz; taglian- accordion; ethnic music